2022
DOI: 10.3389/fimmu.2022.872991
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Subtype Contributes to Distinct Overall Survival for Ovarian Cancer Patients With Platinum-Based Adjuvant Therapy

Abstract: ObjectiveNowadays, platinum-based therapy has been widely used as the first-line therapy of ovarian cancer. However, the effect of the tumor microenvironment on platinum-based therapy remains unclear. In this study, we aim to investigate the relationship between immune microenvironment subtypes and the prognosis of platinum-based therapy in ovarian cancer.MethodsWe integrated 565 ovarian cancer samples from two datasets and obtained the immune subtypes (ISs) by consistent clustering of 1190 immune-related gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Furthermore, CD8 + T cells are known to signify a favorable clinical outcome in a variety of tumors, including OC [ 53 ]. Therefore, combined with previous studies, we found that CD8 + T cells can predict the prognosis of OC patients [ 41 ]. The study also showed that the risk score was negatively correlated with the proportions of resting immune cells but positively associated with immunosuppressive cells, indicating that patients with low-risk scores were immunologically resting, while those with high-risk scores represented an immunosuppressive tumor microenvironment.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, CD8 + T cells are known to signify a favorable clinical outcome in a variety of tumors, including OC [ 53 ]. Therefore, combined with previous studies, we found that CD8 + T cells can predict the prognosis of OC patients [ 41 ]. The study also showed that the risk score was negatively correlated with the proportions of resting immune cells but positively associated with immunosuppressive cells, indicating that patients with low-risk scores were immunologically resting, while those with high-risk scores represented an immunosuppressive tumor microenvironment.…”
Section: Discussionsupporting
confidence: 69%
“…Multiple studies have reported an association between the extent of infiltrating immune cells and the prognosis of OC [ 41 , 42 ]. To analyze the connection between the immune prognostic risk model and immune cell infiltration, the CIBERSORT algorithm was employed to investigate the expression of 22 subpopulations of immune cells in OC tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosine kinase 2 (TYK2), an enzyme that plays a key role in IFN-I signaling, was reduced in abundance in CAOV3 CBPR cells (89). This conclusion was similarly validated by clinical data showing that patients with high IFN-g in the immune microenvironment had a better prognosis in platinum-treated patients (90). Furthermore, it has been shown that cancer cells pretreated by IFN-b were more likely to expose calreticulin and aided immunogenic cell death (ICD) when receiving platinum treatment through the IRF1 pathway (91).…”
Section: Chemotherapymentioning
confidence: 71%
“…Early- and advanced-stage tumors were reported to have different CD45RA + tumor-infiltrating leukocytes (50% vs. 10.5%, respectively) [ 45 ]. Patients from a mesenchymal subtype (derived from immune gene expression subtyping in ovarian cancer) had the lowest tumor purity, a high leukocyte fraction, and a stromal fraction with the highest TGF-β response [ 47 ]. Furthermore, in patients with brain metastasis, it has been found that both the primary and brain metastasis samples contained approximately the same amount of CD45RO + and CD8 + tumor-infiltrating immune cells [ 48 ], similar to that of the study investigating the omental metastasis samples detailed above [ 27 ].…”
Section: Discussionmentioning
confidence: 99%